Plant Cytogenetics Genome structure and chromosome function - Bass, Hank W. (Springer, 2012)
This reference book provides a unique combination of historical and modern subject matter, revealing the central role of plant cytogenetics in plant genetics and genomics as currently practiced. This breadth of coverage, together with the inclusion of methods and instruction, is intended to convey a deep and useful appreciation for the plant cytogenetics.